(untitled) (Indian Journal of Animal Production and Management, 2024)
The present investigation was conducted on newly developed pedometer under NAIP Project in collaboration with IIT Delhi, to correlate find association of activity of Sahiwal bulls (SW) with sexual behaviour and semen production performance at Artificial Breeding Research Centre, ICAR-National Dairy Research Institute, Karnal, Haryana, India. The average pedometer activity of seven bulls was 5421.34±1049.67 and the bulls were divided into two groups, i.e. Group 1 (Four bulls showed lower pedometer activity than average) and Group 2 (three bulls showed higher pedometer activity than average). The data were analyzed by T-test using SAS 9.3. It is evident from the results that pedometer activity (3361.06±482.69 vs.8168.39±802.36), penile protrusion score (1.34±0.08 vs. 1.74±0.08), ejaculatory thrust score (1.48±0.16 vs. 2.38±0.15), mating ability score (70.78±3.23% vs. 83.08±4.58%), ejaculate volume (2.65±0.22ml vs. 4.37±0.26ml), mass activity on scale 1-5 (2.61±0.14 vs. 3.52±0.09), initial progressive motility (65.92±2.79%vs.80.00±1.23%) and sperm concentration (966.50±55.37 million/ml vs. 1352.82±45.59 million/ml) differ significantly (p<0.01) between Group1 and Group 2. Four bulls showed -48.37%, -42.38%, -11.71%, -49.55% less pedometer activity than average, whereas three bulls showed 21.77%, 70.65%, 59.59% higher pedometer activity, respectively. It can be concluded that the bulls showed higher pedometer activity performed better in terms of sexual behaviour and semen quality. Therefore, we can visualize the importance of the use of a pedometer for initial selection of the bulls during breeding soundness evaluation.